An annotated checklist of the marine brachyuran crabs (Crustacea: Decapoda: Brachyura) of India - Trivedi, Jigneshkumar N.; Trivedi, Dhruva J.; Vachhrajani, Kauresh D.; Ng, Peter K. L. (Zootaxa, 2018)
An annotated checklist of the marine brachyuran crabs occurring in India is compiled from published literature and augmented by collections between 2005 and 2015. A total of 910 species belonging to 361 genera and 62 families are herein listed from Indian waters. Specimens representing 130 species were obtained from Gujarat state during 2005 and 2015, of which 23 are new records to Gujarat state and two species are reported for the first time from the west coast of India. The highest number of species were recorded from the Andaman and Nicobar islands (588 species) while the smallest number were from Goa and Karnataka state (82 species). The records indicate that the east coast of India, with 803 species, is more diverse than the west coast, which has 446 species.